Dynamic Conduction in 2-Dimensional Conductor: Magneto-Conductivity Tensor under Rapid Oscillatory Electric Field - Pijus Kanti Samanta (Журнал нано- та електронної фізики)
The conduction mechanism of metals under rapidly oscillating electric field and static perpendicular magnetic field has been investigated within the regime ω≫1/τ. The conventional Lorentz force equation has been used to calculate the conduction current density within the metal. It was found that the conductivity of the metal is anisotropic in nature. We also found that the diagonal elements of the conductivity tensor are equal while the off-diagonal elements are equal in magnitude but opposite in sign. Further it is also found that the diagonal components are imaginary and inversely varies with ω while the off-diagonal components are inversely proportional to ω2.